THE BENEFITS OF USING AN ECLECTIC APPROACH TO ENHANCE CRITICAL THINKING SKILLS - Shukurova Shokhsanam Kakhramon kizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
In the modern world, where information is becoming increasingly accessible and diverse, developing students’ critical thinking is one of the priority tasks of higher education. Critical thinking allows students not only to analyze and evaluate information but also to make informed decisions, which is especially important in professional and academic activities. In the context of teaching foreign languages, particularly English, the development of critical thinking is of particular importance, as it contributes to the formation of communicative competence and intercultural awareness. Traditional teaching methods based on mechanical memorization and reproduction of information are often not effective enough for the development of critical thinking. In this regard, there is a need to use interactive methods that involve active involvement of students in the educational process and the creation of conditions for independent search and analysis of information. This article discusses the features of the use of one of those interactive methods, an eclectic approach, for the development of students’ critical thinking skills in English classes at universities.